MANAGEMENT OF DIABETIC PATIENTS UNDERGOING ORAL SURGERY PROCEDURES: A NARRATIVE REVIEW - Miśkiewicz, Emilia; Borek, Natalia; Gałązka, Julia; Stopa, Ewa; Krupa, Hanna; Wieczorek, Zofia; Kędrak, Magdalena; Stanisławski, Dominik; Jabłońska-Trzosek, Wiktoria; Pochwalski, Jakub (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Diabetes mellitus is a systemic metabolic disorder that requires careful perioperative management in oral and maxillofacial surgery.Aim: To synthesize the current evidence on the perioperative management of diabetic patients undergoing oral surgery, with emphasis on preoperative assessment, glycemic control, medication adjustment, intraoperative precautions, and postoperative care.Material and methods: This narrative review searched PubMed/MEDLINE and Google Scholar using terms related to diabetes mellitus, oral surgery, tooth extraction, perioperative management, glycemic control, HbA1c, antibiotic prophylaxis, wound healing, and postoperative complications. Twenty-three publications met the inclusion criteria.Results: The literature shows that diabetes is a clinically relevant perioperative risk factor in oral surgery. Evidence on extraction healing is mixed: some studies found no significant effect of glycemic control on post-extraction healing, while others reported more unhealed sockets in patients with poorer glycemic control. The available evidence does not consistently support routine antibiotic prophylaxis for simple extractions.Conclusions: Diabetes increases the perioperative risk in oral surgery, however, it is not a contraindication to treatment when patients are properly assessed and prepared. Individualized preoperative evaluation, glycemic control, careful surgical technique, and close postoperative follow-up are essential for safe management of these patients.